PENGARUH SELF CONCEPT DAN SELF CONTROL TERHADAP PERILAKU KONSUMTIF BELANJA ONLINE DI E-COMMERCE - Nurfatimah, Mila; Suherti, Heti; Kurniawan (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2023)
This study aims to investigate the extent to which self-concept and self-control influence online shopping consumptive behavior in e-commerce among students of the Faculty of Education at Universitas Siliwangi, Class of 2019, both partially and simultaneously. The research employs a quantitative survey method with an explanatory survey design. The population comprises all students of the Faculty of Education at Universitas Siliwangi, Class of 2019. The sampling technique used is nonprobability purposive sampling, involving 292 student participants. Data collection is conducted through questionnaires, and the data is analyzed using multiple linear regression analysis. The research findings indicate that: 1) Self-concept significantly influences online shopping consumptive behavior with a significance value of 0.000. 2) Self-control significantly influences online shopping consumptive behavior with a significance value of 0.000. 3) Both self-concept and self-control significantly influence online shopping consumptive behavior with a significance value of 0.000.